Ahruf Sab’ah: Sejarah dan Eksistensinya - Dewi Aprilia Ningrum (JOURNAL OF QUR'AN AND HADITH STUDIES, 2019)
One of the miracles of the Quran is its relevance in every era and time, in the early days of Islam the Arabs had different languages and dialects, even though the message of the Quran can still be conveyed and understood by all Arabs, this is because the Qur'an was revealed with sab’ah ahruf, this paper will discuss the history of ahruf sab’ah and their current existence. Using the literature study this paper concludes that the Quran was revealed with seven harf which were all true and derived from Allah, and during the ‘uthmānī leadership all manuscripts were uniformed with one harf, namely the Manuscripts of uthmānī and all other Manuscripts were burned, then the science of qirā’ah developed  which is a variant way to read the harf of the Quran, therefore the existence of ahruf sab’ah is no longer present, but the science of qirā’ah still exists today.